(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The reforms implemented in the socio-economic, political, spiritual and cultural spheres in our republic require radical renewal and development of education and personnel training system. Therefore, by developing the education system at the level of modern requirements and on the basis of the gained experiences, educating the growing young generation into fully mature and highly moral people who actively participate in the life of the society is one of the top priorities of our country